ANALISIS PUTUSAN TERHADAP GUGATAN PEMBATALAN AKTA HIBAH (STUDI KASUS PUTUSAN PENGADILAN AGAMA - Vincensia Vincensia; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
A grant is a gift from someone to another party that does not have a counter-performance element, the giver gives the right to part or all of his assets to another party without any compensation from the recipient.In legal provisions, a grant that has been given cannot be reclaimed, but there are various exceptions so that the grant can withdrawn or canceled. This research will examine the lawsuit for cancellation of grants made between parents to their children and the legal consequences that arise. The research method in this research is Normative. The approach used is a conceptual approach. Based on the results of the research, it can be concluded that grants must use an authentic deed made by a Notary or PPAT, and in granting grants must pay attention to the provisions of the grant provisions, one of which is the minimum age limit for the grantee. If these conditions are not met, then the legal consequence is that the grant does not have definite legal force.